Islamic Values Integrated in Chemistry Module for Senior Highschool Student in North Sumatera - Mhd Burhan Anggara; Effi Nurma Husnitha; Chintia Dewi Sukri; Ajat Sudrajat; Ramlan Silaban (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
The chemistry module which integrated with Islamic values has already developed in thermochemistry and reaction rate. The aim of this research is to find the availability of Islamic values in student’s handbook, the proper of chemistry module design based on BSNP criteria, and the response to chemistry module which integrated with Islamic values to teacher and university student. This research used the method of research and development. It consists of 3 steps which were analysis, design, and development. The instruments were checklist, questionaire based on BSNP criteria, and response questionnaire. The result shown the lack of Islamic value in student’s handbook, chemistry module design was proper to used because it got the BSNP’s criteria. The teacher and university student’s response are good and need no revision.